Convolution Properties of a Subclass of Analytic Univalent Functions. (2nd February 2014) - Porwal, Saurabh
Abstract : The main objective of the present paper is to investigate some interesting properties on convolution and generalized convolution of functions for the classes R ( n, α ) and R ¯ ( n, α ) . Our results improve the results of previous authors.